Evaluation of a text supported weight maintenance programme 'Lighten Up Plus' following a weight reduction programme: randomised controlled trial. Issue 1 (December 2016) - Sidhu, Manbinder; Daley, Amanda; Jolly, Kate
Abstract Background Many overweight people find it difficult to maintain weight loss after attending a weight reduction programme. Self-weighing and telephone support are known to be useful methods for self-monitoring for weight loss. We examined the effectiveness of an SMS-text messaging based weight maintenance programme to encourage regular self-weighing in adults who had completed a 12 week commercial weight loss programme. Methods Randomised controlled trial of 380 obese or overweight men and women. The intervention group (N  = 190) received a single maintenance support phone call and SMS-text based weight maintenance messages over 12 weeks to encourage regular self-weighing after completing their weight loss programme. The primary outcome was change in weight at 9 months follow up. Results Our sample (N  = 380) had a mean age of 47.4 years (SD 13.4), mean baseline weight and BMI of 93.1 kg (16.1) and 34.4 kg/m2 (5.0) respectively, as well as majority female (87.3 %) and White British (80.0 %). Using intention to treat analysis both groups regained weight at 9 months follow up; the intervention group regained an average of 1.36 kg while the control group regained 1.81 kg. Adjusting for covariates resulted in a mean difference of 0.45 kg (95 % CI −0.78, 1.67) favouring the intervention group at 9 month follow up. Conclusions We found no evidence that an SMS based weight maintenance intervention encouraging adults to weigh themselves weekly prevented weight regain at 3 or 9 months after completing a commercial weight loss programme. Trial Registration Current Controlled TrialsISRCTN47845106 .